Hydroxytriazenes as Indicator for Iron(III): Determination of Iron in Pharmaceutical Samples and Binary Metal Ions Mixtures - C. Sharma, Ratan; Chauhan , R.S.; Purohit, D.N.; Goswami, A.K. (Asian Journal of Chemistry, 2010)
With seven hydroxytriazenes as metallochromic indicators iron (III) could be determined even at very low concentration. The iron contents in pharmaceutical preparations could also be determined accurately.